Chiller Performance Analysis Of Multiple Faults - Rifki Arief Munandar; Nofirman Firdaus; Halim Rusjdi; prayudi prayudi (KILAT, 2020)
Chiller is one source of electricity consumption in buildings. For this reason, keeping the performance of the chiller always at optimum is necessary to limit excessive energy consumption. This paper aims to analyze the performance of the chiller against multiple failures, namely the reduction in condenser and evaporator water that occurs simultaneously (Multiple faults). Secondly, knowing the effectiveness of operating parameters that can detect these multiple failures. In conducting the analysis, we use experimental data conducted by Comstock. The data will be processed and then one variable regression equation will be sought to see the effect of multiple failures on chiller performance and chiller operating parameters to detect multiple failures. From the regression equation for multiple failures we compare it to the normal conditions of the chiller. The results show that for some load ranges, chiller performance drops, while in other ranges chiller performance is better. While the parameters (TCO-TCI) and (TEI-TEO) can detect this multiple failure for the entire load